OVERVIEW OF BURNOUT SYNDROME IN PHYSIOTHERAPY STUDENTS AT POLTEKKES KEMENKES JAKARTA III - Puji Lestari; Diah Lestari (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Burnout is physical, emotional, and mental exhaustion caused by long-term involvement in emotionally demanding situations. In addition to workers, burnout can also be experienced by students. The density of routines and tasks that must be done makes students feel tired physically, emotionally and mentally. A study showed that students who were burnout experienced symptoms of depression, decreased life satisfaction scores, and reduced sleep quality. Burnout gave negative impact not only on the individuals who experience it, but also on the institution. Physiotherapy is one of the majors whose students are prone to burnout. Therefore, the purpose of this study was to find out the picture of burnout in physiotherapy students. This research is a quantitative descriptive study with a cross-sectional design. The respondents to the study were all physiotherapy students of the 2018 class of the Ministry of Health Jakarta III Poltekkes who were taken in total sampling. The method used to measure burnout is using self-report questionnaires, namely the Maslach Burnout Inventory-Student Survey (MBI-SS). The respondents in this study were 24 students. The data analysis is univariate, which is in the form of frequency distribution on the variables studied. The characteristics of the respondents were as follows: the majority were female (75%), 12 students (50%) stated to study in a major that suits their interests, the majority of students come from West Java (58%), and 13 students (54%) have a GPA category with honors, while the rest have a very satisfactory GPA category. The results of the MSI-SS questionnaire analysis showed that 100% of physiotherapy students experienced moderate burnout. In this case, it is possible to have self-efficacy in respondents so that the condition of burnout is not reducing the achievement of academic achievement. The mechanism for coping students against burnout can be both positive and maladaptive, depending on each person. Keywords: burnout, MBI-SS, student, physiotherapy